A retrospective study on the preventive effect of statin after carotid artery stenting. Issue 35 (3rd September 2021) - Liu, Wen; Zhao, Xiong-fei; Liang, Ya-long; Jiang, Chao; Hou, Li-xia; Chen, Xiao
Abstract : Abstract: This retrospective study appraised the preventive effect of statin after carotid artery stenting (CAS). Records were extracted for 100 patients with CAS surgery indicator, aged between 20 and 75 years old, and treated for statin. The cohort study included treatment group (statin and routine treatment) and control group (routine treatment), each group 50 patients. Outcomes consisted of degree of nerve defect (as measured by National Institute of Health Stroke Scale), lipid profiles (mg/dL), and CAS complications within 30 days after surgery. After treatment, there were no significant differences in National Institute of Health Stroke Scale, lipid profiles, and mortality rate between 2 groups. However, significant differences in total cholesterol (mg/dL, P  = .03), low-density lipoprotein (mg/dL, P  = .01), transient ischemic attack ( P  = .03), ischemic stroke ( P  = .04), and cardiac complications ( P  = .03) were identified within 30 days after CAS between 2 groups. The results of this study showed that prior statin treatment may be effective for the prevention of CAS complications.